Fast report: the 2025 Dapu earthquake: simultaneous rupture of mid-crust antithetic thrust fault linkages in the fold-and-thrust belt of Southwestern Taiwan - Cheng-Feng Wu; Ruey-Juin Rau; Ying-Chi Chen (Terrestrial, Atmospheric and Oceanic Sciences)
Abstract The 2025 Dapu earthquake (ML 6.4), which originated from the mid-crustal depths of the fold-and-thrust belt in southwestern Taiwan, provides a significant case study for understanding fault interactions within active tectonic regions. A comprehensive analysis combining fault slip modeling with the spatiotemporal distribution of the aftershocks demonstrates that the rupture associated with the Dapu earthquake conformed to an antithetic thrust fault linkage model. This configuration involves the interaction of two oppositely verging thrust faults, an east-dipping forethrust intersecting a west-dipping backthrust, resulting in complex slip behavior. Velocity waveform data show forward directivity pulses, characterized by large amplitudes and short durations, which support the rupture pattern. The east-dipping fault propagated southeastward, while the west-dipping fault ruptured toward the southwest. Notably, the most severe building damage occurred in the southwestern direction from the hypocenter, highlighting the impact of the rupture directivity along the west-dipping fault. These results suggest that interactions between conjugate fault segments can produce larger and more damaging earthquakes than single-fault rupture. Our research underscores the significance of recognizing complex fault geometries in seismic hazard assessments, especially in fold-and-thrust belt environments where inherited structures play a critical role in rupture dynamics.